Synergistic cytotoxicity between elephantopus scaber and tamoxifen on MCF-7-derived multicellular tumor spheroid - Ho, Wan Yong; Sok, Sian Liew; Yeap, Swee Keong; Alitheen, Noorjahan Banu (Hindawi, 2021)
Elephantopus scaber Linn, a traditional herb, exhibited anticancer properties, and it was cytotoxic against the monolayer estrogen receptor-positive breast cancer cell line, MCF-7, in the previous study. In order to determine the potential of E. scaber as a complementary medicine for breast cancer, this study aimed to evaluate the synergism between E. scaber and tamoxifen in cytotoxicity using MCF-7 in the form of 3-dimensional multicellular tumor spheroid (MCTS) cultures. MCTS represents a more reliable model for studying drug penetration as compared to monolayer cells due to its greater resemblance to solid tumor. Combination of E. scaber ethanol extract and tamoxifen, which were used in concentrations lower than their respective IC50 values, had successfully induced apoptosis on MCTS in this study. The combinatorial treatment showed >58% increase of lactate dehydrogenase release in cell media, cell cycle arrest at the S phase, and 1.3 fold increase in depolarization of mitochondrial membrane potential. The treated MCTS also experienced DNA fragmentation; this had been quantified by TUNEL-positive assay, which showed >64% increase in DNA damaged cells. Higher externalization of phospatidylserine and distorted and disintegrated spheroids stained by acridine orange/propidium iodide showed that the cell death was mainly due to apoptosis. Further exploration showed that the combinatorial treatment elevated caspases-8 and 9 activities involving both extrinsic and intrinsic pathways of apoptosis. The treatment also upregulated the expression of proapoptotic gene HSP 105 and downregulated the expression of prosurvival genes such as c-Jun, ICAM1, and VEGF. In conclusion, these results suggested that the coupling of E. scaber to low concentration of tamoxifen showed synergism in cytotoxicity and reducing drug resistance in estrogen receptor-positive breast cancer.